Pengetahuan Berhubungan dengan Implementasi Kesehatan dan Keselamatan Kerja pada Perawat di RSUD Haji Makassar - Ardiansyah, Ardiansyah; Setiana, Setiana; Amri, Ibnul Aljauzi (Yayasan Mandar Indonesia, 2025)
Hospitals are considered high-risk work environments for occupational accidents. Therefore, the optimal implementation of an Occupational Health and Safety (OHS) system is essential to prevent the occurrence of work-related accidents and illnesses, particularly among healthcare workers serving in hospitals. This study aims to examine the relationship between knowledge and the implementation of Occupational Health and Safety practices. A quantitative method was employed using an analytic approach with a cross-sectional study design, the sample consisted of 69 nurses. The results of this study indicate that good knowledge of Occupational Health and Safety (OHS) is positively related to its implementation at RSUD Haji Makassar. Nurses with good knowledge are more likely to correctly implement OHS standards. Therefore, continuous training on OHS is essential to enhance nurses' awareness and compliance with safety standards. Further research with a larger sample size and direct observational approaches is recommended to understand other factors that influence the implementation of OHS.